A prospective evaluation of thromboelastometry (ROTEM) to identify acute traumatic coagulopathy and predict massive transfusion in military trauma patients in Afghanistan. (13th April 2019) - Cohen, Jared; Scorer, Thomas; Wright, Zachary; Stewart, Ian J.; Sosnov, Jonathan; Pidcoke, Heather; Fedyk, Chriselda; Kwan, Hana; Chung, Kevin K.; Heegard, Kelly; White, Christopher; Cap, Andrew
Abstract : BACKGROUND: Hemorrhage is the leading cause of preventable trauma‐related mortality and is frequently aggravated by acute traumatic coagulopathy (ATC). Viscoelastic tests such as rotational thromboelastometry (ROTEM) may improve identification and management of ATC. This study aimed to prospectively evaluate changes in ROTEM among combat casualties during the first 24 hours and compare the capabilities of our conventional clotting assay (international normalized ratio [INR], >1.2) to a proposed integrated ROTEM model (INR >1.2 with the addition of tissue factor pathway activation thromboelastometry [EXTEM] A5 ≤35 mm and/or EXTEM LI30 <97% on admission) to identify ATC and predict massive transfusion (MT). STUDY DESIGN AND METHODS: This was a prospective observational study of trauma patients treated in NATO hospitals in Afghanistan between January 2012 and June 2013. ROTEM (EXTEM, functional fibrinogen thromboelastometry, APTEM, EXTEM with the addition of a fibrinolysis inhibitor) was performed on admission and at 6 and 24 hours by a designated research team. Treatment teams did not have access to the ROTEM results. RESULTS: ROTEM values were available for 40 male casualties. The integrated ROTEM model classified 15% more patients with ATC than with INR alone and increased the detection of those that required MT by 22%. The sensitivity of the integrated ROTEM model to predict MT was higher than with INR greater than 1.2 (86% vs. 64%); however, specificity with both definitions for predicting MT was poor (38% vs. 50%, respectively). CONCLUSION: These observations support the importance of early identification of and intervention in ATC. Integrating ROTEM into the definition of ATC would increase detection of those requiring MT arguing for its use as an adjunct to clinical presentation in the ultimate decision to initiate MT.